2016
DOI: 10.1177/0734242x16628983
|View full text |Cite
|
Sign up to set email alerts
|

Economic and environmental benefits of landfill gas utilisation in Oman

Abstract: Municipal solid waste disposed in landfill sites decomposes under anaerobic conditions and produces so-called landfill-gas, which contains 30%-40% of carbon dioxide (CO2) and 50%-60% of methane (CH4). Methane has the potential of causing global warming 25 times more than CO2 Therefore, migration of landfill-gas from landfills to the surrounding environment can potentially affect human life and environment. Thus, this research aims to determine municipal solid waste generation in Oman over the years 1971-2030, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Biogas utilization for the energy recovery option was studied at Harmandali Landfill (Izmir/Turkey), and it was suggested that a power plant could generate electricity for approximately 2657 homes based on the size of project to be installed and per capita electricity consumption of 2847 kWh (Cakir et al, 2016;World Bank, 2017). Recently, a study investigated the economic and environmental benefits of LFG utilization in Oman, which has 300 dumpsites and seven engineered landfills (Abushammala et al, 2016). This study found that methane emission capture could attract profits up to US$333 million from the carbon reduction and US$291 million from the electricity generation simultaneously between 2016 and 2030.…”
Section: Askar Landfill's Energy Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Biogas utilization for the energy recovery option was studied at Harmandali Landfill (Izmir/Turkey), and it was suggested that a power plant could generate electricity for approximately 2657 homes based on the size of project to be installed and per capita electricity consumption of 2847 kWh (Cakir et al, 2016;World Bank, 2017). Recently, a study investigated the economic and environmental benefits of LFG utilization in Oman, which has 300 dumpsites and seven engineered landfills (Abushammala et al, 2016). This study found that methane emission capture could attract profits up to US$333 million from the carbon reduction and US$291 million from the electricity generation simultaneously between 2016 and 2030.…”
Section: Askar Landfill's Energy Assessmentmentioning
confidence: 99%
“…Higher energy demand and environmental degradation due to the use of fossil fuels were motives to explore new sources of renewable energy and consequently to minimize adverse impacts on environmental resources, human health and sustainability. Previous studies have investigated the recovery of energy from landfill sites to generate electricity (Abushammala et al, 2016;Cakir et al, 2016;Rodrigue et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no treatment facilities in Oman, and consequently dumping waste into the landfill is the only ultimate way to dispose solid waste. Disposal of waste in landfills results in the generation of huge amounts of GHG, has a negative impact on human health and causes air and water pollution (Abushammala et al, 2016). Oman's current waste management system is struggling to handle the growing amounts of waste and this issue is difficult to resolve if Oman purely focuses on waste disposal (Ithraa, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gas generation at an active landfill is continuous, unlike solar and wind power. Hence, LFG combustion can act as buffer when there is cloud cover or low wind velocity (Abushammala et al, 2016).…”
Section: Environmental Benefitsmentioning
confidence: 99%